Non-print media [soundrecording] - Minow, Newton N. (Development Digest premier series, 1973)
In-depth discussion of the history and the role of educational and cable television. Explains the rationale behind past rulings of the Federal Communications Commission as well as pending legislation. In an extensive question and answer session, suggests that one solution to the pollution crisis is to reduce unnecessary transportation by working, educating, and even shopping at home through cable television.